Collagen Scaffolds in Bone Sialoprotein-Mediated Bone Regeneration - Thomas E. Kruger; Andrew H. Miller; Jinxi Wang (The Scientific World Journal)
Decades of research in bioengineering have resulted in the development of many types of 3-dimentional (3D) scaffolds for use as drug delivery systems (DDS) and for tissue regeneration. Scaffolds may be comprised of different natural fibers and synthetic polymers as well as ceramics in order to exert the most beneficial attributes including biocompatibility, biodegradability, structural integrity, cell infiltration and attachment, and neovascularization. Type I collagen scaffolds meet most of these criteria. In addition, type I collagen binds integrins through RGD and non-RGD sites which facilitates cell migration, attachment, and proliferation. Type I collagen scaffolds can be used for bone tissue repair when they are coated with osteogenic proteins such as bone morphogenic protein (BMP) and bone sialoprotein (BSP). BSP, a small integrin-binding ligand N-linked glycoprotein (SIBLING), has osteogenic properties and plays an essential role in bone formation. BSP also mediates mineral deposition, binds type I collagen with high affinity, and binds αvβ3 and αvβ5 integrins which mediate cell signaling. This paper reviews the emerging evidence demonstrating the efficacy of BSP-collagen scaffolds in bone regeneration.